The contribution of monetary institutions to stability: The Swiss case - Ernst Baltensperger (Aussenwirtschaft, 2017)
This article studies Swiss monetary policy of the 19th and 20th century to understand the Swiss Franc's strength and stability. The continued appreciation against other currencies over the course of a century went hand-in-hand with Switzerland's political and social consolidation as well as its increasing economic success. Political institutions arose from people's beliefs and convictions, granting them credibility. In Switzerland, these institutions have been a major force in creating an environment that has permitted the Swiss National Bank to successfully pursue its course of monetary stability.
Keywords: 330